Does financial inclusion strengthen the fintech-growth nexus? Evidence from small and medium enterprises - Rahayu, Wati; Najeela Pakutandang, Fayza (Journal Economic Business Innovation, 2025)
Purpose: This study will contribute to the understanding of how adoption of FinTech, access to finance and financial inclusion jointly affect firm growth through direct, mediating and moderating pathways.Method: A survey-based quantitative methodology and hierarchical regression analysis were used to test the hypotheses and model relationships.Findings: The findings indicate that FinTech adoption has strong positive impact on access to finance, which in turn affects firm growth. Greater financial inclusion multiplies the effect of FinTech use and growth, suggesting that inclusive financial systems enhance the gains from digital transformation. The mediation analysis additionally shows that financial access mediates the FinTech–growth nexus to some extent, implying that FinTech enhances firm performance in a direct way by means of technological efficiencies as well as indirectly via financial accessibility. These results highlight the strategic significance of fintech in shaping firms’ financial behavior, competitiveness and value.Novelty: The integrated approach in this study combines Financial Intermediation Theory, Financial Inclusion Theory, and the Technology Acceptance Model providing a comprehensive view of how FinTech leads to firm growth. It contributes to empirical knowledge by identifying financial inclusion as a moderating factor between digital transformation and financial access.Implications: The results underscore that strengthening digital financial infrastructure, encouraging inclusive policies, and improving financial literacy are critical for optimising the socioeconomic contribution of FinTech innovation to firm development and resilience.